Going Concern Audit of Manufacturing Companies: A Study Before and During the Covid-19 Pandemic - Muhammad Fadila Laitupa; Elna Marsye Pattinaja; Sukma Rahmi Ayu Patty (Khazanah Sosial, 2023)
This study aims to determine the effect of Profitability, Leverage and Company Growth on the receipt of going concern audit opinions before and during the Covid-19 pandemic. Research using exploratory study with the type of data used is quantitative data. Population data in this study for 2019-2020 from manufacturing companies listed on the Indonesian Stock Exchange (IDX). Research data that was dialyzed amounted to 238 of 119 samples of manufacturing companies. Purposive sampling is one of the techniques used in research for sampling. The sampling technique used purposive sampling with data analysis techniques, namely descriptive statistics and logistic regression. Based on the results of this study shows that (1) Profitability before the COVID-19 pandemic did not affect the acceptance of Going concern audit opinions, (2) Profitability during the Covid-19 pandemic affected the receipt of Going Concern Audit Opinions, (3) Leverage before the COVID-19 pandemic does not affect the going concern audit opinion, (4) Leverage when the COVID-19 pandemic affects the going concern audit opinion, (5) Company growth before the COVID-19 pandemic does not affect the going concern audit opinion, (6) Company growth during the COVID pandemic -19 does not affect the going concern audit opinion.